Police and duty lawyer perceptions of domestic violence protection order proceedings involving parents: towards greater system accountability and family-centred decision-making - Stambe, Rose-Marie (Journal of family violence, 2023)
Purpose: Domestic violence (DV) is a problem of global significance and remains a gendered issue that disproportionately affects women and children. Prevalence studies on women’s experiences of DV suggest that around 50% of victims identify as mothers. The effects of DV on mothers and children are well documented, raising implications for their protection. Civil protection orders are a legal tool used to reduce and prevent experiences of DV. Research on protection order effectiveness is mixed with research suggesting that the ongoing relationship between a respondent and aggrieved parent around child contact presents ongoing opportunities for re-victimization. This study contributes to the scant literature on the implications of protection orders on parental responsibilities. Method: The study draws on surveys with duty lawyers and focus groups with police officers. A thematic analysis was used to examine perceptions and experiences of ‘no contact’ protection orders and respondent parent non-compliance where mutual children are involved. Results: Findings suggest that ambiguous ‘no contact’ conditions and a lack of clarity around their implications for child contact play a key role in respondent parent non-compliance, ranging from uninformed non-compliance to the strategic use of children as a form of coercive control in non-compliance. Conclusion: Findings raise implications for specialist legal advice and support for parents affected by DV to sit alongside protection order court proceedings. Findings highlight the need for greater system accountability to ensure court-issued protection orders take a family-centred approach that align with parental responsibilities and ensure child and adult victims’ safety and wellbeing.